Pengaruh Penerapan Metode PECS (Picture Exchange Comunication System) Terhadap Kemampuan Membaca Huruf Hijaiyah Anak Asd (Autism Syndrom Disorder) Di SD Muhammadiyah 1 Karanganyar - Maryanti, Maryanti; Rinawati, Atim; Maryanto, Maryanto (Tarbi: Jurnal Ilmiah Mahasiswa, 2026)
This study aims to determine how the process of applying the PECS (Picture Exchange Communication System) method and how the PECS method influences reading hijaiyah letters for autistic children in SD Muhammadiyah 1 Karanganyar, Karanganyar sub-district, Kebumen district, Central Java. The design of this research is Pre-Experimental. This research is a quantitative study which was carried out with 6 trials of applying phase I to phase III. The subjects in this meeting were 8 children with autism special needs students with different categories, where 3 children were categorized as severe autism, 2 children were categorized as moderate autism and 3 children with mild autism category. The instrument used is a PECS Picture Exchange Communication System test sheet from phase I to phase III. The data analysis technique used the Paired Sample T-test to determine the relationship between variables X and Y. Based on the results of the study, the average value before the PECS method was carried out was 80.87 on the test results after the PECS method was 83.12. where the results show Sig. (2-tailed) 0.02 < 0.05 it can be concluded that the PECS method has a significant influence on the ability of autistic students to read hijaiyah letters.